The role of administrative empowerment in the development of human competencies in economic institutions An analytical study of the opinions of a sample of individuals working in Algeria Telecom in Laghouat - Bendouma, Safia; Laidani, Ilyes (Dirassat Journal Economic Issue, 2020)
The study aimed to identify the role of administrative empowerment in the development of human competencies in economic institutions, by conducting a field study that included a sample of individuals working in Algeria Telecom in Laghouat, the descriptive and analytical method was adopted and the questionnaire was used as a tool for collecting and distributing data to the sample. we also used the SPSS statistical program to analyze the questionnaire and the multiple linear regression method to test the study hypotheses. The study concluded that there is a statistically significant effect between the administrative empowerment and the development of human competencies.